Exploiting Human NK Cells in Tumor Therapy - Vacca, Paola; Pietra, Gabriella; Tumino, Nicola; Munari, Enrico; Mingari, Maria Cristina; Moretta, Lorenzo (Frontiers in Immunology, 2020)
NK cells play an important role in the innate defenses against tumor growth and metastases. Human NK cell activation and function are regulated by an array of HLA class I-specific inhibitory receptors and activating receptors recognizing ligands expressed de novo on tumor or virus-infected cells. NK cells have been exploited in immunotherapy of cancer, including: 1) the in vivo infusion of IL-2 or IL-15, cytokines inducing activation and proliferation of NK cells, that are frequently impaired in cancer patients. Nonetheless, the significant toxicity experienced, primarily with IL-2, limited their use except for combination therapies, e.g. IL-15 with checkpoint inhibitors. 2) The adoptive immunotherapy with cytokine-induced NK cells had effect in some melanoma metastases (lung), while other localizations were not affected. 3) A remarkable evolution of adoptive cell therapy is represented by NK cells engineered with CAR targeting tumor antigens (CAR-NK). CAR-NK cells complement CAR-T cells as they do not cause GvHD and may be obtained from unrelated donors. Accordingly, CAR-NK cells may represent an “off-the-shelf” tool, readily available for effective tumor therapy. 4) The efficacy of adoptive cell therapy in cancer is also witnessed by the αβT cell- and B cell-depleted haploidentical HSC transplantation in which the infusion of donor NK cells and γδT cells, together with HSC, sharply reduces leukemia relapses and infections. 5) A true revolution in tumor therapy is the use of mAbs targeting checkpoint inhibitors including PD-1, CTLA4, the HLA class I-specific KIR, and NKG2A. Since PD-1 is expressed not only by tumor-associated T cells but also by NK cells, its blocking might unleash NK cells playing a crucial effector role against HLA class I-deficient tumors, that are undetectable by T-cells.